Sustainable Islamic Education: Contribution of Islamic Law to Ecologically Aware Education - Nurjanah, Nurjanah; Gettari, Trie Rahmi; Afroo, Fakhriyah Annisa (An-Nuha, 2025)
The global environmental crisis underscores the critical role of education in fostering sustainable ecological awareness. Islamic education holds strategic potential by integrating Islamic legal values—such as the concept of the caliphate, the principle of maslahah, and the prohibition of environmental destruction—into efforts to promote environmentally responsible behavior. This study aims to examine the contribution of Islamic law to the development of environmentally conscious Islamic education and to identify models for its integration into the curriculum. Employing a qualitative descriptive method with a normative-pedagogical approach, the research draws on literature related to Islamic legal sources, curriculum documents, and sustainable education frameworks. The findings indicate that Islamic legal values can be effectively applied through thematic learning, environment-based projects, and the reinforcement of ecological ethics in Islamic educational institutions. The study concludes that the synergy between Sharia principles and contemporary educational strategies is essential for cultivating a generation of environmentally conscious Muslims dedicated to environmental sustainability.